2019
DOI: 10.1016/j.jclinepi.2019.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Baseline health status and setting impacted minimal clinically important differences in COPD: an exploratory study

Abstract: Objectives: Minimal clinically important differences (MCIDs) are used as fixed numbers in the interpretation of clinical trials. Little is known about its dynamics. This study aims to explore the impact of baseline score, study setting, and patient characteristics on health status MCIDs in chronic obstructive pulmonary disease (COPD). Study Design and Setting: Baseline and follow-up data on the COPD Assessment Test (CAT), Clinical COPD Questionnaire (CCQ), and St. George's Respiratory Questionnaire (SGRQ) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 74 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Another potential weakness is suggested by a recent study, which found that MCID estimates of health status questionnaires can vary significantly depending on baseline patient characteristics/disease severity. 59…”
mentioning
confidence: 99%
“…Another potential weakness is suggested by a recent study, which found that MCID estimates of health status questionnaires can vary significantly depending on baseline patient characteristics/disease severity. 59…”
mentioning
confidence: 99%
“…Thereby, we designed this quality of life based study to investigate the clinical outcomes of using HFCWO as an adjunctive therapy for COPD as measured by using the St. George's Respiratory Questionnaire for COPD Patients (SGRQ-C) which is a disease speci c instrument designed to measure the impact on overall health, daily life, and perceived well-being in patients with COPD 13 . This has been an extensively validated questionnaire and often used to evaluate the advantage of a new treatment for COPD 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Given that clinical outcomes can vary from one patient to another, the MCID has garnered attention as a clinically meaningful threshold value above which the outcome is deemed relevant by the patient. While many studies have examined the MCID, there has been a notable absence of research evaluating the MCID after post-stroke acute care programs [ 12 , 13 , 14 ]. Enhancing our understanding of the MCID and identifying factors that predict deterioration in the MCID can significantly impact the definition of worse outcomes and the development of shared decision-making methods.…”
Section: Introductionmentioning
confidence: 99%